Establishment and evaluation of strength criterion for clayey silt hydrate-bearing sediments. Issue 6 (19th March 2018) - Li, Qingchao; Cheng, Yuanfang; Li, Qiang; Zhang, Chuang; Ansari, Ubedullah; Song, Benjiang
ABSTRACT: Appropriate strength criterion is the prerequisite for wellbore stability analysis. In this paper, the Modified Mohr-Coulomb criterion that considering the effects of hydrate is established based on the experimental results of the artificial clayey silt samples with hydrate. Meanwhile, the new criterion was evaluated by comparing the differences in the safe lower limit of drilling mud density calculated by both the traditional and modified Mohr-Coulomb criteria. The result demonstrates that the mud density window calculated by the new criterion is narrower, which reveals the applicability of the modified Mohr-Coulomb criterion in the analysis of wellbore stability in hydrate formation.